Sesquiterpene lactones from Geigeria aspera : isolation, cytotoxicity against murine muscle cell lines and microsomal metabolism - Botha, C.J. (Christoffel Jacobus) (University of Pretoria, 2021)
Dissertation (MSc (Veterinary Sciences))--University of Pretoria, 2020.